Analisis Faktor yang Berhubungan dengan Kunjungan Ibu Balita di Posyandu Kelurahan Rejowinangun Utara Kecamatan Magelang Tengah Kota Magelang - Widiyanti, Aulia; Wahyono, Bambang (Indonesian Journal of Public Health and Nutrition, 2023)
Background: Toddler period experiences a process of rapid growth and increased nutritional needs, so mothers of toddlers are advised to visit Posyandu (Integrated Healthcare Center) to check the growth and development of toddlers, in order to anticipate if there are developmental disorders of toddlers that are not according to their age. North Rejowinangun Village experienced a decrease in the percentage of children under five compared to every year, in 2020 the achievement of toddlers was calculated to be 40.62% and in 2021 it was 22.53%. The purpose of this study was to determine the factors associated with the visit of mothers of children under five to the posyandu. Methods: This study used an analytic observational type with a cross sectional design. The number of samples was 91 respondents, the sampling technique used two stage cluster sampling and the data were analyzed by Chi Square test. Results: statistical tests showed that the variables were age (p = 0.096), education level (p = 0.0001), occupation (p = 0.041), knowledge (p = 0.0001), distance traveled (p = 0.0001), family support (p = 0.0001) and the role of cadres (p = 0.0001). Conclusion: there is a relationship between education level, level of knowledge, occupation, distance traveled, family support and the role of cadres with maternal visits to posyandu. There is no relationship between age and mother's visit to posyandu.